Operation improvement measures of dry type air-core reactor in severe cold environment. (August 2020) - Wang, Lin; Hao, Wenguang; Deng, Junyu; Wang, Hongyu
Abstract: In severe cold environment, the surface of dry type air-core reactor would easily be cracked, once natural contamination accumulated on the cracks, surface flashover would have more possibility to happen, leading to more serious reactor faults. The most commonly used methods to avoid reactor surface discharge includes RTV coating and surface decontamination using water-based cleaning agent, yet the effects of these methods, as well as possible impact on reactor performance have not been fully studied. In this paper, RTV coating and decontamination tests were carried out to evaluate the effect of the methods, also the impact of these two methods on reactor electrical performance were analyzed. The research result showed that: (1)Water-based cleaning agent was effective in removing contamination on insulation paint surface, but less effective in removing contamination on RTV coated surface; However, the water-based cleaning agent would cause damping between the winding strands, and damping recovery degree was not easy to control. Therefore, water-based cleaning agent was not suitable to solve surface flashover problem of dry type air-core reactors. (2) The overall coating for reactor surface and air duct could be realized by special spraying equipment. The adhesion test showed that RTV was of good covering and adhesion performance, and had little impact on reactor temperature rise, indicating that RTV could be an effective measure to improve operation quality of dry type air-core reactor in extreme cold environment.